Contributions of Non-Farm Employment Opportunities on Household Income: Study on Itinerant Vegetable Traders in Sumowono Village - Hardati, Puji; Rijanta, R; Ritohardoyo, Su (Komunitas, 2015)
This study aims to analyze the contribution of non-farm employment opportunities to household income. The experiment was conducted in the Sumowono Village, Semarang Regency Central Java province. Respondents were itinerant vegetable traders and community leaders. Data collection is carried out by means of in-depth interviews. The analysis showed that non-farm employment opportunities in rural areas conducted by itinerant vegetable traders became one of alternative employment and contribute to labor force participation. Generally itinerant vegetable vendor is male. Mostly are married, have an average of two children, and only 20 percent is unmarried. The majority of junior high school education is finished. Reach of the work area is varies, begin from the surrounding villages in the sub-district, outside the district, regencies and outside the province. Motorcycle become one of the means of transportation used. The outpouring of working time each day an average of 9 hours. Contribution to household income by 70 percent.       Penelitian bertujuan menganalisis kontribusi kesempatan kerja non-pertanian terhadap pendapatan rumahtangga. Penelitian dilaksanakan di Desa Sumowono Kabupaten Semarang provinsi Jawa Tengah. Responden adalah pedagang sayur keliling dan tokoh masyarakat. Pengumpulan data dilaksanakan dengan cara wawancara mendalam. Hasil analisis menunjukkan bahwa  kesempatan kerja non-pertanian di perdesaan yang dilakukan oleh pedagang sayur keliling menjadi salah satu alternatif kerja dan berkontribusi terhadap partisipasi angkatan kerja. Umumnya pedagang sayur keliling berjenis kelamin laki-laki. Sebagian besar berstatus kawin, dengan rata-rata memiliki anak 2 orang, dan hanya 20 persen bujang. Pendidikan mayoritas adalah tamat sekolah lanjutan pertama. Jangkauan wilayah kerja bervariasi, mulai dari desa sekitar satu wilayah kecamatan, luar kecamatan, luar kabupaten dan luar provinsi. Sepeda motor menjadi salah satu alat transportasi yang digunakan. Curahan waktu kerja setiap hari 9 jam. Kontribusi terhadap pendapatan rumahtangga sebesar 70 persen.